PENGUKURAN KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM MEMBANGUN KARAKTER SISWA - Basri, - - (Universitas Pendidikan Ganesha, 2017)
Learning leadershipthat combines self awareness, self regularly, and value based leadership becomes an answer to find out the figure of leader who is able to implement value system to their followers. The purposes of research are to examine how important is virtues of learning ladership and to examine multidimensionality of learning leaderhip. Result shows that learning leadership isa suitable type of leadership to implement the value system effectively for grow of sudents character. Result also shows that learning leadership is a unidimensional construct.Keywords: measuring, learning leadership, students character